Self-Efficacy, Demographic Characteristics and Organizational Citizenship Behavior among Management Employees in Public Organizations in Kenya - Rotich , Richard (European Journal of Business and Strategic Management, 2022)
Purpose: Government institutions through it employees play a vital role in steering and implementing government's vision and policy for the benefit of the citizens. However, the work habits of many government employees to have failed to meet public expectations thus perennial complaints. Globally, Self-efficacy and Organizational Citizenship Behavior are concepts commonly researched and practiced among private sector organizations for better work performance. Although, these constructs have not received favorable consideration among public sector scholars and practitioners in the Africa, entrenching positive work behavior among employees for improved service delivery is universal and widely advocated for in the literature. It is a day today responsibility of managers, however studies have bestowed this role in the organization in general rather than the actual drivers of positive work behavior. The purpose of this study was to examine whether self-efficacy and the demographic characteristics of senior public officers influence their engagement in citizenship behaviors. Methodology: Guided by social exchange theory and social cognitive theory, the study adopted a cross sectional quantitative survey design. Target population was the middle level employees in public service in Kenya. Data was collected using questionnaires, (N=389) determined by stratified sampling procedure and analyzed to derive descriptive and inferential statistics using SPSS computer software. From the multiple regression model (1), R2 = 0.042 showing that demographic characteristics accounted for 4.2% variation in OCB, while model (2) shows R2 =0.17 indicating that Self-efficacy accounted for 17.1% of OCB. Self-efficacy had significant relationship with Organizational citizenship behavior (Î²1= 0.362, p<0.05). Age had a positive significant relationship (Î²= .204, p<0.05) with OCB. Tenure was found to relate negatively with OCB (Î²= -.183 (p<.05). Findings: The findings showed that Self-efficacy and age were strong determinant of OCB, thus the higher the employees' age and psychological and emotional self-belief the higher their tendency to exhibit extra role behavior at the work place. Employee's practice of discretionary behaviour to help colleagues solve organizational or personal problems is not just a matter of chance but a fully conscious decision informed of ones' personal characteristics. Unique Contribution to Theory, Practice and Policy: The study affirmed the applicability of the social exchange and social cognitive theories among public sector workers. As such, managers in public institutions should strive to identify, promote and nurture employee's personal traits that contribute to practice of positive work behaviours like citizenship behaviour at the work place in their endeavor to improve public service delivery.